2022
DOI: 10.1186/s12951-022-01522-6
|View full text |Cite
|
Sign up to set email alerts
|

Huc-MSCs-derived exosomes attenuate inflammatory pain by regulating microglia pyroptosis and autophagy via the miR-146a-5p/TRAF6 axis

Abstract: Background Chronic inflammatory pain significantly reduces the quality of life and lacks effective interventions. In recent years, human umbilical cord mesenchymal stem cells (huc-MSCs)-derived exosomes have been used to relieve neuropathic pain and other inflammatory diseases as a promising cell-free therapeutic strategy. However, the therapeutic value of huc-MSCs-derived exosomes in complete Freund's adjuvant (CFA)-induced inflammatory pain remains to be confirmed. In this study, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…Our rescue experiment testified that miR-146a-5p downregulation can activate the further exacerbation of pancreatitis and activate the NLRP3 signaling pathway through the target TRAF6. Other studies have also confirmed that downregulation of TRAF6 by miR-146a-5p regulates pyroptosis and autophagy [17,32,33]. Therefore, miR-146a-5p may become a nucleic acid drug for inhibiting acute pancreatitis, which requires us to further conduct animal experiments and clinical trials.…”
Section: Discussionmentioning
confidence: 93%
“…Our rescue experiment testified that miR-146a-5p downregulation can activate the further exacerbation of pancreatitis and activate the NLRP3 signaling pathway through the target TRAF6. Other studies have also confirmed that downregulation of TRAF6 by miR-146a-5p regulates pyroptosis and autophagy [17,32,33]. Therefore, miR-146a-5p may become a nucleic acid drug for inhibiting acute pancreatitis, which requires us to further conduct animal experiments and clinical trials.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, some studies have shown that microRNAs carried by exosomes participate in regulating autophagy (Hua et al, 2022;Luo et al, 2021). Recent studies have shown that follicular fluid-derived exosomal microRNA-18b-5p regulates the PI3K/Akt/mTOR signaling pathway inhibiting the development of polycystic ovary syndrome (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Follicular fluid EVs, which fill the ovarian follicle and influence oocyte developmental competency, can originate from the oocyte, cumulus, or mural granulosa cells in the ovarian follicle [ 28 ]. Initially, it was reported that huc-MSCs-derived exosomes could activate autophagy via miR-146a-5p/TRAF6 [ 29 ]. Breast cancer cell-derived exosomes were also reported to induce autophagy of breast cancer cells by transferring miR-1910-3p [ 30 ] while gastric cancer cell-derived exosomes were found to induce the autophagy of neutrophils via HMGB1/TLR4/NF-κB signaling [ 31 ].…”
Section: Discussionmentioning
confidence: 99%